Making Copyright Content Available in the Cloud vs the Making of Copies: Revisiting Optus TV and Aereo - Foong, Cheryl (2015)
In the digital environment, the commercialisation of copyright content is increasingly led by access to content, rather than the provision of copies. Copyright law nevertheless remains fixated on copies, or more specifically, copyright owners’ exclusive reproduction right. This unwavering fixation on copying blinds us to the potential afforded by the right to make works available to the public, a broad right introduced in 1996 by the WIPO Internet Treaties to address the interactive communication channels afforded by the internet. The default approach in cases involving “cloud”-based services is to overlook the “act” of making available, and stretch the reproduction right to encompass the activities of a service provider. As a result, the scope of the making available right remains uncertain and its potential unrealised. Using prominent Australian and US cases — NRL v Singtel Optus and ABC v Aereo — this article illustrates the importance of clearly conceptualising the “act” of making available, which allows courts to allocate responsibility for primary infringement of the making available right in a principled manner, without unduly restricting the development of innovative services in the cloud.